2012
DOI: 10.1016/j.physa.2011.07.049
|View full text |Cite
|
Sign up to set email alerts
|

The Full Strategy Minority Game

Abstract: The Full Strategy Minority Game (FSMG) is an instance of the Minority Game (MG) which includes a single copy of every potential agent. In this work, we explicitly solve the FSMG thanks to certain symmetries of this game. Furthermore, by considering the MG as a statistical sample of the FSMG, we compute approximated values of the key variable {\sigma}2/N in the symmetric phase for different versions of the MG. As another application we prove that our results can be easily modified in order to handle certain kin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Ho et al redefined a Gini index for the M G [19] which showed that whenever the reduced variance takes its minimum value, the inequality among the agents is maximized. In a recent work [15], we studied crowd region and presented a calculation of σ that matched the simulation results. This calculation was based on the FSMG (Full Strategy Minority Game), an imaginary instance of the MG where all the possible agents (let call N ) participate in the game.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Ho et al redefined a Gini index for the M G [19] which showed that whenever the reduced variance takes its minimum value, the inequality among the agents is maximized. In a recent work [15], we studied crowd region and presented a calculation of σ that matched the simulation results. This calculation was based on the FSMG (Full Strategy Minority Game), an imaginary instance of the MG where all the possible agents (let call N ) participate in the game.…”
Section: Introductionmentioning
confidence: 93%
“…In [20] we showed that a MG with a deterministic rule to play in case of a tie of the strategies for which the SPTD (Strict Period Two Dynamics, the P T D with probability equal to 1) for even occurrences of the states is met, is a periodic game. For example, it applies to the M G prior where agents have an a priori favorite strategy to use in case of tie.…”
Section: The Underlying Network Of the Minority Gamementioning
confidence: 99%
See 3 more Smart Citations